Extracellular Redox State Regulates Catecholamine Biosynthesis in PC12 Cells with Insulin Resistance - Zheng, H. L.; Yan, S. M.; Hu, D. H.; Zhang, X.; Zhang, Y. T.; Guan, Q. H.; Ding, Q. L. (Hormone and Metabolic Research, 2014)
Extracellular cysteine (Cys)/cystine (CySS) redox potential (Eh) plays a crucial role in maintaining redox homeostasis and an alteration of redox state occurs in various physiological conditions, including diabetes, cancer, and aging. This study was designed to determine whether a variation in extracellular redox state would alter the function of insulin-resistant PC12 cells. Various redox states were established by providing different extracellular Cys/CySS Eh to insulin-resistant PC12 cells. We intensively investigated the relationship between redox state and catecholamine biosynthesis in PC12 cells, and evaluated the changes in cellular reactive oxygen species (ROS), catecholamine (CA) synthesis, tyrosine hydroxylase (TH) expressions, and the activity of rate-limiting enzyme in CA synthesis by using DCF-fluorescence, HPLC, and the real-time PCR, respectively. We also determined the protein levels of NF-E2-related factor 2 (Nrf2), a redox sensitive transcription factor, using an ELISA assay. We found that the oxidized Cys/CySS Eh (0 mV) pretreatment decreased CA, TH, and Nrf2 levels, but induced ROS overproduction. Insulin induced a significant increase in CA synthesis and ROS production, blocked by more reducing redox conditions. The paradox of CA and TH alterations between insulin and 0 mV groups may be attributed to degree of redox imbalance as evidenced by different ROS levels in 2 groups, which is further confirmed by CA alterations in different concentrations of hydrogen peroxide. Additionally, dithiole-3-thione (D3T, an inducer of Nrf2) corrected 0 mV-induced TH inhibition. In conclusion, CA biosynthesis in insulin-resistant PC12 cells could be influenced by extracellular Cys/CySS redox effects on cellular redox sensitive transcription factors.
Keywords: tyrosine hydroxylase; redox balance; Cys/CySS Eh; reactive oxygen species